2006
DOI: 10.1590/s0101-81752006000200032
|View full text |Cite
|
Sign up to set email alerts
|

Does predator benefits prey? Commensalism between Corynoneura Winnertz (Diptera, Chironomidae) and Corydalus Latreille (Megaloptera, Corydalidae) in Southeastern Brazil

Abstract: Commensalism between Corydalus Latreille, 1802 (Megaloptera, Corydalidae) and Corynoneura Winnertz, 1846 (Diptera, Chironomidae, Orthocladiinae) larvae was recorded in Indaiá stream, at 1,380 m a.s.l. (Parque Nacional da Serra do Cipó, 19º-20ºS, 43º-44ºW) and in the headwaters of São Francisco river, at 1,300-1,700 m a.s.l. (Parque Nacional da Serra da Canastra, 20º00'-20º30'S, 46º15'-47º00'W), in Minas Gerais state, Brazil. Seventy eight Corydalus larvae (range 22-88 mm) were sampled: 61 in the Indaiá stream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…Gut content analyses revealed that the most abundant chironomid taxon was Corynoneura, but larvae of Larsia, Rheotanytarsus and Tanytarsus, were recorded as well. Likewise, Corynoneura was the most abundant and frequent chironomid larvae on megalopteran larvae body, as found by Callisto et al (2006), i.e., Corynoneura is the most available larvae for Temnocephala. It is noteworthy that we found two megalopteran larvae harbored both Corynoneura larvae and temnocephalan worms.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…Gut content analyses revealed that the most abundant chironomid taxon was Corynoneura, but larvae of Larsia, Rheotanytarsus and Tanytarsus, were recorded as well. Likewise, Corynoneura was the most abundant and frequent chironomid larvae on megalopteran larvae body, as found by Callisto et al (2006), i.e., Corynoneura is the most available larvae for Temnocephala. It is noteworthy that we found two megalopteran larvae harbored both Corynoneura larvae and temnocephalan worms.…”
mentioning
confidence: 51%
“…As for temnocephalan-host associations, interactions between chironomids and their host have been recorded involving a great array of animals (Roque et al 2004;Marques et al 2008), mainly insects, such as megalopteran larvae (Callisto et al 2006).…”
mentioning
confidence: 99%
“…Two individuals of K. colossica were also collected bearing larvae of both morphospecies of Nanocladius (Fig. 1-C & De La Rosa, 1995;Pennuto et al, 2002;Pennuto, 2003), Asia (Hayashi, 1998) and from the Brazilian states of São Paulo, Minas Gerais and Amazonas (Roque et al, 2004;Callisto et al, 2006). Corydalus larvae carrying Chironomidae were collected in riffles in a 2 nd order tributary of the Cascatinha River, in Nova Friburgo (RJ), at 1300 m a.s.l.…”
Section: Resultsmentioning
confidence: 99%
“…(Orthocladiinae) on fishes of the families Astroblepidae and Loricariidae (Freehofer & Neil, 1967;Fittkau, 1974;Mendes et al, , 2007Sydow et al, 2008); Nanocladius (Plecopteracoluthus) sp. on Plecoptera (Dorvillé et al, 2000) and Ephemeroptera (Callisto & Goulart, 2000;Pepinelli et al, 2009); Thienemanniella on Megaloptera (Callisto et al, 2006); Rheotanytarsus on Odonata (Ferreira-Peruquette & Trivinho-Strixino, 2003;Rosa et al, 2009), and Coleoptera (Segura et al, 2007). Roque et al (2004) listed new occurrences of phoretic Chironomidae-larvae living on different aquatic animals, mainly for the state of São Paulo.…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrates the one-way facilitating direction, termed 'commensalism', that an interspecific interaction can have (Connell, 1983). It has been found that Chironomidae often display commensalistic interactions to increase their feeding opportunity, mobility, protection from disturbance and reduce predation risk (Tokeshi, 1993;Callisto et al, 2006), but this entails interactions with other orders of aquatic invertebrates. Within-class commensalism has not been found or described for many aquatic invertebrates, yet could have a large explanatory value when it comes to niche expansion and range shifts (Bulleri et al, 2016).…”
Section: Neutral and Negative Effects Of Biotic Interactionsmentioning
confidence: 96%